Implementation of an intervention towards altering the self-concept in physical education - Oswald, Esther; Valkanover, Stefan; Conzelmann, Achim (Swiss Journal of Educational Research, 2018)
Studies of interventions fostering self-concept development often omit to report information on implementation conditions. The present study contributes to overcome this deficit, by investigating the implementation frequency and the effects of an interventionaimed at improving childrens’ self-concept within a physical education (NTeachers = 16, NStudents = 309). Results reveal that physical education is being taught in an individual-oriented and reflexive way. The frequency of the implementation depends on the teacher’s professional experience. Frequent intervention implementation is linked with significant change in students’ self-concept, but not with perceived physical ability.